2021
DOI: 10.3390/su13116112
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Key Variables on the Way to Wellbeing in the Transition from Face-to-Face to Online Higher Education due to COVID-19: Evidence from the Q-Sort Technique

Abstract: This paper reports perceptions of higher education lecturers who switched from classical face-to-face teaching to online teaching due to the unexpected circumstances caused by the COVID-19 pandemic. Based on a validated theoretical model about the roles of instructors in online settings, the authors document the perceptions of experienced face-to-face lecturers regarding their performance in online roles and the perceived importance of the formal and informal support they received during the process of adaptin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 82 publications
1
9
0
2
Order By: Relevance
“…For instance, ref. [22] suggests that, during the transition from face-to-face teaching mode to eLearning, there is a general need for teacher training on embedding life skills into teaching. A third important aspect is the content being delivered in eLearning.…”
Section: Sustainable Education and Elearningmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, ref. [22] suggests that, during the transition from face-to-face teaching mode to eLearning, there is a general need for teacher training on embedding life skills into teaching. A third important aspect is the content being delivered in eLearning.…”
Section: Sustainable Education and Elearningmentioning
confidence: 99%
“…Specifically, refs. [21][22][23] argue that eLearning using some online platforms such as MOOCs can help promote human rights and democratic values, thus contributing to SDGs. The authors of [24] also find teacher presence plays a critical role in using gamification to teach sustainability knowledge with eLearning.…”
Section: Sustainable Education and Elearningmentioning
confidence: 99%
“…Su éxito necesita el compromiso de los estudiantes y debe ser dinámico, ofreciendo comentarios personalizados de profesores, foros de discusión, pruebas con retroalimentación inmediata y clases con materiales de lectura (Torres et al, 2021). En añadidura, el éxito pedagógico también se debe al apoyo educativo que reciben los docentes tanto de los organismos oficiales (universidades) como de entidades no formales (personas dentro y fuera de su universidad), para abordar las tareas de aprendizaje y enseñanza del desarrollo (P. Gómez et al, 2021).…”
Section: Introductionunclassified
“…This adaption has been incredibly challenging, especially in developing countries, where teachers and organizations, in some cases, do not have the proper means to implement distance education lectures effectively [2]. For example, a recent study that analyzed vital elements, from the instructor's point of view, in the transition from faceto-face learning to online learning reported that traditional instructors have difficulties implementing the role of life skills promoter (relevant according to the UNESCO humanistic vision of universities) [3]. Following UNESCO's suggestions, many institutions have taken advantage of the benefits provided by technologies common to distance education.…”
Section: Introductionmentioning
confidence: 99%